Formulation and Stability of Microemulsion Preparations From Secang Wood Extract (Caesalpinia Sappan L) and Virgin Coconut Oil (VCO) - Ani Setyopratiwi; Fathru Naban Rahman; Niko Prasetyo (CV. Syntax Corporation Indonesia, 2024)
Research has been conducted to make microemulsion preparations from virgin coconut oil (VCO) and secang wood extract. The purpose of this study was to determine the characteristics of secang wood extract with ethanol solvent, determine the Hydrophilic Lipophilic Balance (HLB) value of a mixture of three surfactants that can form the most stable microemulsion preparations, and determine the most optimal variation in the concentration of secang wood extract in secang microemulsion formulations.This study began with the manufacture of secang wood ethanol extract from secang wood powder and 96% ethanol, then tested for flavonoid levels. Furthermore, VCO microemulsions in a mixture of water with secang extract are made with variations in HLB values, namely 12, 13, 14, and 15. Microemulsions with HLB variations were tested for stability through organoleptical observations and turbidity values by storage treatment at room temperature, heating, and centrifugation. Microemulsions were also tested for free fatty acid (FFA) levels. After that, the preparation of microemulsions with the most stable HLB is carried out with variations in the concentration of secang wood extract in the formulation. Microemulsions with extract variations were tested for stability through organoleptical observation and turbidity values after 24 hours, heating, and centrifugation. Microemulsions with optimal concentrations of secang wood extract were tested for antioxidant activity. The secang extract produced from the extraction was reddish-brown in color and had total flavonoids equivalent to 230.6 mg QE/g samples. The most stable microemulsion from this study is a microemulsion with an HLB value of 15 with a ratio of water:extract:VCO:surfactant which is 65:2,5:2,5:30. The microemulsion features transparent red, 1 phase, and smells like Tween 80 with turbidity value below 1% during storage, heating, and centrifugation with microemulsion FFA value of 0.53%. Based on variations in the concentration of secang wood extract, the higher the concentration of the extract, the more unstable the microemulsion produced. The 3% secang extract microemulsion is the most optimal microemulsion with antioxidant activity (IC50) of 1.4573±0.2694 mg/mL.